2019
DOI: 10.18280/rcma.290601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Metallic Pseudo Rubber-Silicon Rubber Composite for Three-Way Seismic Isolation

Abstract: This paper mainly carries out the preliminary work for the design of an innovative three-way seismic isolator based on the metallic pseudo rubber-silicon rubber (MPR-SR) composite. First, the MPR-SR composite was prepared by adding the SR, a high-molecular polymer, to the MPR, and several MPR-SR specimens of different molding densities were prepared. Next, the specimens were subjected to compression and shear tests under quasi-static and dynamic loads, respectively. Several tests were carried out to reflect ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In general, the main parameters for evaluating the seismic stability of a slope include acceleration, velocity, and displacement. Among them, the acceleration response of the slope and its distribution law are the basic data for evaluating the dynamic response of the slope under the action of seismic load (Marzoratia et al 2012;Nova-Roessig and Sitar 2016;Li and Cai 2020;Luo et al 2020;Zhao and Dong 2020;Zhao et al 2019;Shibata and Nagao 2020;Michalowski and You 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the main parameters for evaluating the seismic stability of a slope include acceleration, velocity, and displacement. Among them, the acceleration response of the slope and its distribution law are the basic data for evaluating the dynamic response of the slope under the action of seismic load (Marzoratia et al 2012;Nova-Roessig and Sitar 2016;Li and Cai 2020;Luo et al 2020;Zhao and Dong 2020;Zhao et al 2019;Shibata and Nagao 2020;Michalowski and You 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous compressive tests on the MR [22], the stress-strain curve of the specimen (temperature: room temperature; loading frequency: 1Hz; relative density: 0.27; maximum strain amplitude: 20%) in the last cycle was divided into a loading segment and an unloading segment. Then, the loading segment was fitted piecewise by the LS method, producing the lines OA and OB in Figure 1.…”
Section: Constitutive Model Of Mrmentioning
confidence: 99%
“…Related research tested the seismic resistance of cracked walls reinforced with carbon fiber cloths. Compressive and shear tests were conducted on masonry specimens constructed with materials used in ancient buildings and reinforced by grouting, and concluded that the grouting had improved the mortar performance, integrity and strength of the masonry specimens [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%